The association between preoperative plasma D-dimer levels and early postoperative outcomes in patients with esophageal cancer - Seyfollah Rezaei; Seyed Ziaeddin Rasihashemi; Shahriar Hashemzadeh (Journal of Research in Clinical Medicine, 2021)
Background: The present study aimed to evaluate the efficacy of plasma D-dimer levels in predicting early morbidity and mortality in patients with esophageal cancer. Methods: for this purpose, 60 patients who did surgery for middle- (n=35) and lower-thoracic esophageal cancer (n=25) were recruited. Then, preoperative plasma D-dimer levels were measured in a quantitative and qualitative manner and their relation with postoperative outcomes in each type of cancer was assessed for six months. Results: With regard to the middle-thoracic esophageal cancer, complications were observed in 14 cases and deaths were reported in six individuals. Considering the lower type, morbidity was found in 11 cases and mortality was seen in five patients. In both types of cancer, plasma D-dimer levels were significantly higher in patients with complications or deaths compared with those who were not. Sensitivity, specificity, as well as positive and negative predictive value (P/NPV) of plasma D-dimer levels were 90.91%, 78.57%, 76.92%, and 91.67% for diagnosing morbidity of the lower-thoracic esophageal cancer and 80%, 85%, 57.14, 94.44% for predicting mortality in this type of cancer. Moreover, the given values were equal to 71.43%, 76.19%, 66.67%, and 80% for diagnosing complications of the middle-thoracic esophageal cancer and 83.3%, 72.41%, 38.46%, 95.45% in predicting deaths induced by this type of cancer. Conclusion: It was concluded that elevated plasma D-dimer levels could be accompanied by adverse events and early poor postoperative outcomes for esophageal cancer.